A new alternative for reconstruction of soft triangle defects secondary to burn injury: Superiorly based columellar flap - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
Nasal reconstruction following severe burn injury remains a challenge in plastic surgery. In burn patients, the external nares and the soft triangle are commonly affected subunits of the nose where local tissue deficit and scar contraction during the recovery period contribute to soft triangle deformity and alar stenosis. These patients usually have associated facial burns with varying severity, which significantly limit the availability of local flaps. Reconstruction with skin grafts often yields unsatisfactory results because of the mismatch in colour and texture in addition to the primary and secondary contraction phenomena. The use of superiorly based columellar flap, which has yielded satisfactory results on a female patient, would be a new and reliable option for reconstruction of the soft triangle deficit with alar stenosis. (C) 2010 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Columellar flap; Soft triangle; Burn injury; Nose; NASAL DEFECTS; NOSE; GRAFTS